Brand Uses for Self Alignment (footing) in Social Interactions - Leão, André Luiz Maranhão de Souza; Mello, Sérgio Carvalho Benício de; Freitas, Grayci Kelli Alexandre de (Review of Business Management, 2011)
There has been much debate concerning how consumption has become the core trigger for change within contemporary society. In this sense, it is believed that, in contemporary times, it is through consumption that identities are formed, emphasizing that it is not the consumed object that has the ability to express identities but what which it represents. Thus, it is possible to deduce that the consumption of brands is a mainstay of the construction of identities. Assuming the premise that the self is a social construction wrought in the otherness and that in social interactions this construction goes through a continuous process of alignment (footing) The present study aimed to understand how consumers align their self while turn to brands as symbolic resources. With this in mind, we have developed this exploratory study. For such, an ethnography of communication was undertaken through participant observation of people daily interaction of different social groups. Our results indicate the self alignment through twenty four brand activities. At the end, we analyze implications of our study for the academy as for the brand management. Key words: Brands. Consumption. Footing. Self. Ethnography of communication.